ANALISIS DAMPAK PEMBELAJARAN VIRTUAL SEBAGAI TINDAKAN PENCEGAHAN COVID-19 DI PERGUTUAN TINGGI - Eri Susanto (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
This research was conducted to determine the impact of virtual learning as a preventive measure for COVID-19 in higher education. This research uses the basis of qualitative methods with literature studies from several sources, both printed and electronic, as well as accredited scientific journals. The article criteria used in this study are articles that describe virtual learning in college students and have a complete section. The search mechanism is using the Google Scholar database using the keywords "the impact of COVID-19 in higher education" and "virtual learning". The research technique used is the documentation technique, which can be in the form of treatises, newspapers, essays, scientific papers, literature or journal articles. The validity test that the researchers used was a triangulation of data sources. Analysis of the literature review with 4 stages, namely by collecting data, reducing data, displaying data and drawing conclusions. The results of this study are; (1) virtual-based learning is believed to be one of the keys for higher education to emerge from the prolonged pandemic crisis, (2) virtual learning based on the Online Learning Model (OLM) can increase the absorption of student material towards course material with an increase in percentage reaching more than 81 % compared to only using face-to-face learning models, (3) virtual learning also has shortcomings, first, limited mastery of technology by educators and participants; second, inadequate facilities and infrastructure; third, limited and uneven internet access; fourth, inadequate budget provision; Fifth, when viewed from a student's point of view, this online-based lecture activity will burden the student quota expenses and finally, there are learners' losses in the assessment process.